Analysis and Exploration of the Current Situation of Modern Landscape Architecture Planning and Construction Problems — Taking Zhuhai Yuanming New Garden as an Example - Junzhang Chen; Yile Chen; Liang Zheng (Formosa Journal of Sustainable Research, 2022)
This paper discusses and analyzes the current situation of domestic urban landscape architecture planning and design, and takes the Yuanming new garden, a typical modern landscape architecture in Zhuhai, as an example. Based on the bibliometric analysis and the fund research analysis of Wanfang Data Kehui platform, this paper combs the frontier and development trend of the current landscape architecture planning and design research. Secondly, through the field investigation of Zhuhai Yuanming new garden and the visual analysis of the data platform, this paper discusses the current situation, problems in planning practice, and suggestions to be improved.